Adaptación del inventario de estilos de aprendizaje de Kolb - Escurra Mayaute, Luis Miguel (1992)
The purpose of this paper is to present the adaptation of Kolb Inventory of Cognitive Styles. The study was carried out with 250 psychology students of both genders from two universities of Lima. A pilot study indicated the need to adapt the instrument. The psychometric analysis included a study content validity and construct validity through the iner-test method. The results showed that the inventory, in its Lima version, has validity ad reliability